Pengembangan Media Pembelajaran Berbasis Lingkungan Pada Materi Bahasa Arab di Madrasah Tsanawiyah Nurus Syam Wringin Bondowoso - Firdaus, Sulton; Yusuf, Muhammad; Munir, Misbahul (Faidatuna, 2023)
Learning Arabic using environment-based media is a way to bring students or learners closer to the material studied in the real world so that it is connected to their daily lives. This approach is expected to reduce students' learning difficulties and improve the achievement of learning objectives. This study aims to develop environment-based learning media for Arabic language materials at Madrasah Tsanawiyah Nurus Syam Wringin Bondowoso. The research method used is research and development. The validators consisted of material experts, Arabic language experts, and learning media experts. The results of this study created an Environment-based learning module for Arabic language material called "درس اللغة العربية" Arabic Language Learning Grade VII, with product assessment reaching a validity level of 4.36 (very good) by material experts, 4.35 (very good) by linguists, and 4.35 (very good) by media experts and the practicality of the development product getting an assessment of 4.35 with "very good" criteria. The results of the limited trial assessment showed a score of 4.40 (very good), while in the phase II trial, the score increased to 4.51 with "very good" criteria..